2022
DOI: 10.1108/jedt-07-2021-0372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of indoor air quality on teacher performance using artificial neural network

Abstract: Purpose A building's Indoor Air Quality (IAQ) has a direct impact on the health and productivity on its occupants. Understanding the effects of IAQ in educational buildings is essential in both the design and construction phases for decision-makers. The purpose of this paper is to outline the impact air quality has on occupants' performance, especially teachers and students in educational settings. Design/methodology/approach This study aims to evaluate the effects of IAQ on teachers' performances and to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…There is limited detailed research on indoor air quality (IAQ) within educational buildings in the Middle East (Alzahrani et al, 2023). In Jordan, most architectural educators in governmental universities observed and noted that the students' productivity during design studio hours does not meet their minimum expectations.…”
Section: Architectural Design Studiomentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited detailed research on indoor air quality (IAQ) within educational buildings in the Middle East (Alzahrani et al, 2023). In Jordan, most architectural educators in governmental universities observed and noted that the students' productivity during design studio hours does not meet their minimum expectations.…”
Section: Architectural Design Studiomentioning
confidence: 99%
“…The studio environment includes the physical environment (climate, geographical characteristics and immediate context such as technological tools availability) and sociocultural and psychological factors (Berivan and Bahar, 2020). Physical environment concerns IAQ, daylight and artificial light and personal space; all create thermal, visual and personal comfort (Mandala, 2019;Alzahrani et al, 2023;Kaushik et al, 2021).…”
Section: Studio Environment and Students' Productivitymentioning
confidence: 99%
“…The indoor air quality (IAQ) is an essential factor affecting the health and comfort of the occupants of a building [9][10][11][12] and the occupants' behavior [13]. Saidin et al [9] identified that the indoor concentrations of PM 2.5 and CO 2 significantly contribute to the total hazard ratio and that the ventilation system significantly affects the indoor air quality, using a case study of six bank offices located in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Saidin et al [9] identified that the indoor concentrations of PM 2.5 and CO 2 significantly contribute to the total hazard ratio and that the ventilation system significantly affects the indoor air quality, using a case study of six bank offices located in Malaysia. Alzahrani et al [10] assessed the impact of the IAQ parameters (relative humidity (RH), ventilation rates, and carbon dioxide) on teachers' performance in Saudi Arabia and used an artificial neural network (ANN) to predict the relationship between performance and IAQ. In one study [11], three indoor air pollutants (PM 2.5 , CO 2 , and CO) were measured in six public health centers, and identified that ventilation is a key measure to improve the IAQ.…”
Section: Introductionmentioning
confidence: 99%